2017
DOI: 10.1371/journal.pone.0183435
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR-16 as an endogenous reference gene for the normalization of urinary exosomal miRNA expression data from CKD patients

Abstract: Chronic kidney disease (CKD) is a severe disorder with an increasing incidence worldwide. An early detection may help to prevent its progression and to minimize the risk of cardiovascular diseases as one of the major comorbidities. Recently, extracellular miRNAs like urinary exosomal miRNAs became of great interest as non-invasive biomarkers which can be determined by RT-qPCR. But until now, there is no consensus regarding the normalization of miRNAs isolated from body fluids. The present study analyzed the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 51 publications
2
66
0
Order By: Relevance
“…As these results suggested transcriptional regulation of miRNA expression in L. pneumophila infection, as opposed to changes in miRNA processing, the pri-miRNA expression levels of miR-146a, miR-155, miR-125b, and miR-221 were analyzed by qPCR. pri-mir-16 served as an endogenous control (33,34). Upregulation of pri-mir-155 and -146a ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As these results suggested transcriptional regulation of miRNA expression in L. pneumophila infection, as opposed to changes in miRNA processing, the pri-miRNA expression levels of miR-146a, miR-155, miR-125b, and miR-221 were analyzed by qPCR. pri-mir-16 served as an endogenous control (33,34). Upregulation of pri-mir-155 and -146a ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, 12 miRNAs and one small RNA (U6 snRNA) were selected for stability analysis (Table 1) [8,[48][49][50][51][52][53][54][55]. 2.6.…”
Section: Candidate Rg Selectionmentioning
confidence: 99%
“…Yu et al found that the renal tubule-derived urinary exosomal miR-200b could regulate the progression of renal fibrosis, eventually leading to CKD [126]. Lange et al concluded that miR-16 derived from urinary exosomes was the most stable endogenous reference gene in patients with CKD [127].…”
Section: The Role Of Exosomes In Vascular Aging Related Kidney Diseasesmentioning
confidence: 99%